2022
DOI: 10.1167/iovs.63.12.7
|View full text |Cite
|
Sign up to set email alerts
|

Pregabalin Mediates Retinal Ganglion Cell Survival From Retinal Ischemia/Reperfusion Injury Via the Akt/GSK3β/β-Catenin Signaling Pathway

Abstract: Purpose Progressive retinal ganglion cell (RGC) loss induced by retinal ischemia/reperfusion (RIR) injury leads to irreversible visual impairment. Pregabalin (PGB) is a promising drug for neurodegenerative diseases. However, with regard to RGC survival, its specific role and exact mechanism after RIR injury remain unclear. In this study, we sought to investigate whether PGB could protect RGCs from mitochondria-related apoptosis induced by RIR and explore the possible mechanisms. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 62 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…In addition, we found that Rh‐GFFYE can stabilize the mitochondrial membrane potential, which can reflect the function of mitochondria as the site of ROS production. [ 22,44 ] Thus, these results suggest that Rh‐GFFYE nanofibers suppress oxidative stress, which is an early event in RIR injury.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In addition, we found that Rh‐GFFYE can stabilize the mitochondrial membrane potential, which can reflect the function of mitochondria as the site of ROS production. [ 22,44 ] Thus, these results suggest that Rh‐GFFYE nanofibers suppress oxidative stress, which is an early event in RIR injury.…”
Section: Discussionmentioning
confidence: 78%
“…As previously reported, intracellular ROS production is dramatically elevated under OGD conditions. [ 22 ] Thus, we also evaluated the effects of Rh‐GFFYE and the control compounds on the intracellular ROS level. The cellular ROS levels in R28 cells were assessed by 2′,7′‐dichlorofluorescin diacetate (H 2 DCF‐DA) assay using confocal laser scanning microscope (CLSM) observation (Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…S1). Additionally, OPs have also been used to sensitively monitor retinal ischemic effects by detecting changes before any alterations in b-waves occur [25][26][27]. The amplitudes of OPs in the experimental eyes, particularly in the 60-minute ischemia and 7-days reperfusion group, significantly decreased to less than 50% of those in the sham eyes (Fig.…”
Section: Silicone Wire Embolus Insertion Interrupts Retinal Blood Flowmentioning
confidence: 99%